Thoughts of life and social perspectives reflected in short vignettes of Banaful/ বনফুলের অনুগল্পে জীবনভাবনা ও সামাজিক দৃষ্টিকোণ (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
Banaful is one of the mostly noticeable and popular Author in the Bengali literature. His actual name is Balai Chand Mukhopadhyay. He was attentive about writing from his Childhood. He disguised himself by this pen name to keep his identity secret. He was a fiction writer, playwright, poet and essayist. By profession he was a doctor. He left his imprint of identity by writing innumerable poems, novels, short stories and essays. He was born on 19th July 1899 at village Monihari in Purnia district of Bihar of undivided India. Banaful wrote more than one Thousand of poems. Moreover, he composed 60 movels, near about 600 short stories, 5 dramas and lots of essays. He came in contact with familiar unknown people of different communities and different occupations coming every day to the Ganga Ghat and railway station adjacent to his house. The stories of those people evolved fluently in various compositions of Banaful and enriched his literature. Like Banaful, his father was also a doctor, and he was associated with social welfare work and various newspapers. Banaful's bountiful scientific attitude and heuristic conception made his literature at the peak of originality and individuality. His curious vision at human life and human characters made his writings filled with diversity and novelty. He portrayed subtle incidents of real life through simple stories. In short stories, he used simple languages with explicit messages. In Bengali the word 'Banaful' suggests 'collection of wild flowers'. Literally his compositions are also enriched with colourful artistry.Banaful composed different shapes of short stories. The smallest short stories he composed are often just a half to one or two pages long. Banaful was mostly enthusiastic to compose these-format of shortvignettes. His short vignettes are free from dramatic and wordy sentences. Instead of fictitious words, he used deeply meaningful short words and sentences, which reflects the stories of real life. Banaful was a realistic author indeed. His level of drimagination did not incline to differ from reality. Most of his short stories creates deep thought attraction. By narrating a simple, trivial incident he gave a detailed account of harsh life reality. Most of his short vignettes are the manifestation of simplicity. In a few short meaningful sentences, he unveiled many complex issues of human life and character. His stories are the reflections of the experiences he had acquired throughout the life. In his short stories, Banaful beautified various feelings and emotions of human life in a new way, new style. His short stories begins with the descriptions of simple neglected matters or incidents. But at the end of the story, only one or two sentences revealed the original flavour of the story. Banaful's short stories portrayed the greater meaning of the life.
Keywords: Imprint of identity; scientific attitude; heuristic conception; diversity; short vignettes; subtle incidents; wild flowers; colourful artistry; trivial incidents; harsh life reality